Usulan Perbaikan Tata Letak Fasilitas dan Peralatan Kerja pada UD Dua Dewi - Amaliatus Sholicha; Teguh Oktiarso; Purnomo Purnomo (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2022)
This study focuses on improving the design of facility layout and work equipment to enhance productivity by efficiently utilizing production floors and designing ergonomic equipment. The proposed facility layout was developed using blocplan, and evaluation criteria included adjacency score, rail dist score, R-score, and distance of material transfer. The ninth alternative was chosen, with an adjacency score of 0.62, rail dist score of 993.43, R-score of 0.85, and a material transfer distance of 71.83 meters. Regarding work equipment design, an anthropometric approach was used to design chairs and tables that are ergonomic. The proposed chair design has a height of 396.1 mm, seat width of 422.6 mm, seat length of 348.4 mm, back height of 531.5 mm, and back width of 423.25 mm. The proposed table has a height of 656 mm, width of 1276.1 mm, and length of 6135 mm. The study demonstrates that improving the design of facilities and work equipment can significantly improve productivity and employee comfort, emphasizing the importance of ergonomics in workplace design. The findings of this study can be useful for companies seeking to improve productivity through facility and equipment design.